Socio-technical Perspective on End-of-life Vehicle Recovery for a Sustainable Environment - Tze Fong Go; Dzuraidah Abd Wahab; Zuhair Fikri Fadzil; C.H. Azhari; Y. Umeda (International Journal of Technology, 2016)
End-of-life Vehicle (ELV) recovery is a promising strategy to minimize the environmental impact of automotives on environmental sustainability. This study aims to assess the community’s knowledge from a socio-technical perspective on ELV. A survey was conducted in Japan and Malaysia to assess public perception on ELV recovery. The results showed that the communities in both countries have basic knowledge and a reasonably good level of awareness on environmental issues and recovery strategies such as recycling. However, there is a high level of uncertainty on the concept of ELV reuse and remanufacturing, as more than 50% of respondents were unsure of their willingness to participate in ELV initiatives. The respondents agreed that the industry and government should take the necessary steps to support the reuse strategy. The paper concludes with suggestions from a socio-technical perspective, which aim to ensure an effective implementation of ELV recovery through reuse and remanufacturing.